Linguistic Means of Expressing Humour in the Music Parodies by the Galician Project “Páramo Pictures” - Marina Snetkova (Ибероамериканские тетради, 2018)
The purpose of this article is to analyze the linguistic means of expressing the retranca – the subtle humour which is considered to be typical of the Galicians – in the music parodies by the project “Páramo Pictures”, whose video clips have become rather famous in the region during the last five years.The study method we apply is based on the linguo-stylistic, cultural and semiotic analysis of the audiovisual text.The songs, which “Páramo Pictures” choose to parody, are usually recent hits that have well-known video clips: “Despacito” by Luis Fonsi, “Súbeme la radio” by Enrique Iglesias, “Wrecking Ball” by Miley Syrus, etc. They film new videos trying to reproduce the elements of the original plot, but adapting both the lyrics and the scenery to rural Galicia.The success of the project can be explained by the perfect use of all the elements of the audiovisual text, stereotypes about rural Galicia, and – in terms of linguistics – of the wordplay and the homophonic translation, all of which shows the effective interaction of the analogy and the contrast, two essential components of the genre of the parody.